Occupational Stress on Special Education Teachers at Inclusive School X, South Tangerang - Uthami, Nurul; Sunardi, Sunardi (Angstrom Centre of Education, 2022)
Occupational stress on teachers is an unpleasant experience that causes disturbances encountered by someone who has a role as a teacher (general teacher or special education teacher). This study aimed to see the level of occupational stress experienced by special education teachers at Inclusive School X. This research focused on ten special education teachers who teach at Inclusive School X. The research used a mixed method with a qualitative (descriptive) and a quantitative (questionnaire) approach. The results showed that the special education teachers at Inclusive School X experienced a moderate stress level. This can be seen from the symptoms suffered by the special education teachers at the school. Some teachers decided to join in a counseling session with a psychologist because they felt symptoms of stress affecting their psychology. At the same time, some other teachers experienced physical health problems. This study strongly suggests the school stakeholders’ take steps to overcome teacher occupational stress levels as this will affect the teachers’ performance at the school. The steps may include program conduction to deal with the stress at work for the teachers.